2002
DOI: 10.1200/jco.2002.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Exploratory Analysis of the Association Between Tumor Response, Quality of Life, and Expenditures Among Patients Receiving Paclitaxel Monotherapy for Refractory Metastatic Breast Cancer

Abstract: Patients with evidence of tumor response on paclitaxel had a QoL benefit not observed in nonresponders, and this response was associated with a trend for lower overall costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
(11 reference statements)
2
14
0
1
Order By: Relevance
“…Also objective tumor progression was not correlated with deterioration of QOL during chemotherapy, except for social functioning. Using another questionnaire, Modi et al [6] found that tumor response was significantly associated with early improvement in QOL score in refractory breast cancer. Several limitations are noted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Also objective tumor progression was not correlated with deterioration of QOL during chemotherapy, except for social functioning. Using another questionnaire, Modi et al [6] found that tumor response was significantly associated with early improvement in QOL score in refractory breast cancer. Several limitations are noted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Plus récemment, dans une étude sur 50 patientes déjà traitées pour leur cancer du sein métastatique et recevant une chimiothérapie par paclitaxel, les patientes répondeuses après deux cycles ont une amélioration signifi cative de la qualité de vie non retrouvée chez les patientes non répondeuses [40]. L'amélioration de la qualité de vie est parfois plus fré-quente que la réponse à la chimiothérapie.…”
Section: Taux De Réponse Réduction Des Symptômes Et Qualité De Vieunclassified
“…4,5 Although a significant number of advanced cancer patients respond to first-line regimens, survival rates continue to remain fairly low, with the main outcome being largely palliative. 2,6,7 Nevertheless, it is becoming apparent that treatment may improve quality of life even if it does not lengthen it. 8 In today's treatment milieu, physicians face uncertainty as to whether palliative tumor reduction is worth the cost of potential negative symptom or quality of life disruption that often occur secondary to treatment toxicity.…”
mentioning
confidence: 99%
“…[1][2][3] However, progress has been incremental over several decades, and nevertheless the great majority of people with metastatic or recurrent cancer will die from their disease. 4,5 Although a significant number of advanced cancer patients respond to first-line regimens, survival rates continue to remain fairly low, with the main outcome being largely palliative.…”
mentioning
confidence: 99%
See 1 more Smart Citation